World Bank Engagement at the State Level : The Cases of Brazil, India, Nigeria and Russia - World Bank (World Bank, Washington, DC, 2012)
Beginning in the late 1990s, the World Bank significantly expanded its engagement at the state level in Brazil, India, Nigeria, and Russia. This pilot cross-country study reviews the selected cases of World Bank's lending and analytic work at the state level in those four large federated countries. In each case, state governments were the Bank's principal development partners. The study looks at the evolution of the four country strategies and the Bank's mode of engagement at the state level, in order to draw lessons from that experience both for the Bank and for its federal and state partners. State-level engagement posed several strategic and operational questions, among them which states to engage, the scope of engagement, and the modalities of engagement. The Bank set out its approach to selecting states in country strategy documents. The findings are worth highlighting. First, the study confirms the desirability of continued selective Bank lending in a few states. However, the poverty impact of those interventions could be enhanced by balancing states' propensity to reform and the concentration of poverty within them, giving greater weight to the needs of poorest states. Second, continued focus on public finance management as the core area appears sound, irrespective of whether engagement is confined to this area or serves as an entry point for broader engagement. And third, there is considerable scope for greater impact from analytic work, knowledge transfer, and expanded knowledge sharing not so much concepts and theories as practical experience of what works and what does not.